2013
DOI: 10.1021/jp4071482
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Seed Nanolayers for Enhanced Nucleation of Nanocrystalline Diamond Thin Films

Abstract: ABSTRACT:The enhancement of the nucleation and subsequent growth of nanocrystalline diamond (NCD) films with a submicron thickness control on silicon substrates is demonstrated by using a sputter deposition of six different metallic (Cr, Mo, Nb, Ti, V, and W) seed nanolayers. The effectiveness of altered surface morphology and surface chemistry is discussed. We show that the number density of nanodiamond particles embedded on the nanorough metallic surfaces after an ultrasonic seeding step together with the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The choice of water over ethanol was necessary due to its higher viscosity, in order not to leak through the printer nozzles. Nonetheless, from Figure b, we estimated a high seeding density of the order of ≈10 10 cm −2 , which is a desirable order of magnitude to enable the growth of fully closed thin‐films of only 100–200 nm thickness, with good adhesion to the substrate and low surface roughness …”
Section: Resultsmentioning
confidence: 97%
“…The choice of water over ethanol was necessary due to its higher viscosity, in order not to leak through the printer nozzles. Nonetheless, from Figure b, we estimated a high seeding density of the order of ≈10 10 cm −2 , which is a desirable order of magnitude to enable the growth of fully closed thin‐films of only 100–200 nm thickness, with good adhesion to the substrate and low surface roughness …”
Section: Resultsmentioning
confidence: 97%
“…The clustered C atoms in the subsurface region of TM powders and the type of TM seed powders used influence the nucleation process. Seeding with W, Mo, and Nb powder on a silicon (Si) substrate, the carbides form rapidly, along with the film's highest nucleation density and columnar structure [ 3 ]. Itoh et al demonstrated that a small-sized seeding powder would result in higher nucleation density due to the more significant number of grains than a larger-sized powder for a given weight percent of powder.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, several studies have focused on controlling the grain nucleation process through the use of seed layers or isolated seed crystals. The seed layers/crystals have been found to alter the nucleation kinetics [5], enhance epitaxial growth [6], and aid the growth of highly oriented polycrystalline films [7]. However, these techniques have only been used to control a narrow set of microstructural parameters in specific materials and their wider applicability is unclear.…”
Section: Introductionmentioning
confidence: 99%